Success Stories of Caring for Premature Babies From the Experiences of Indonesian nurses: A Qualitative Descriptive Study - Herlina, Herlina; Rustina, Yeni; Wanda, Dessie (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Premature birth is still a crucial problem for children worldwide. In Indonesia, the 5th highest preterm birth rate country, there have been many studies conducted on the success of treating premature babies but more often research on an intervention to address a specific problem faced by premature infants and their families. Rarely, the research examines qualitatively how health workers, including nurses, take careful measures to address all the health problems of premature babies at the same time until they are successful in caring for premature babies.Purpose: This study aims to dig deeper into the success of Indonesian nurses in caring for premature babies.Methods: This research is a qualitative descriptive study using focus group discussions (FGD) to obtain data from 17 nurses in the nursery who have experience caring for premature babies. Data from the two FGD groups were recorded, transcribed, and analyzed using thematic analysis.Results: Four themes were obtained which described the success of nurses in caring for premature babies, namely (1) the various feelings of nurses when caring for premature babies (2) the attitude of nurses to work (3) the support of nurses to families (4) the work output of nurses.Conclusion: Success in caring for premature babies from a nurse's perspective is successful in returning the baby to a healthy condition and staying healthy while being treated at home without rehospitalization. The success of caring for premature babies requires cooperation between nurses and families. Nurse support for the family will enable the family to participate actively during care and be able to care for premature babies at home.